Molecular diagnostics in dermatology and dermatopathology - Murphy, Michael J. (Current clinical pathology, 2011)
Molecular Diagnostics in Dermatology and Dermatopathology presents the basics of molecular biology and molecular diagnostic methods most commonly used in the clinical laboratory, with an emphasis on the concepts and testing most relevant to dermatological diseases. Topics include the integration of newer diagnostic and prognostic techniques with ?traditional? histologic approaches, and discussions of regulatory, ethical, legal, economic issues and ?newer? technologies. This important diagnostic tool outlines the clinically relevant uses (i.e.; diagnostic, staging and/or prognostic) applications of these techniques in the field of dermatology. Molecular studies that investigate the pathogenesis of skin diseases will be excluded, unless they also have a direct diagnostic utility. The book will be of interest to practicing pathologists, dermatology and pathology residents, dermatologists, and dermatopathologists.